2014
DOI: 10.1074/jbc.m113.545376
|View full text |Cite
|
Sign up to set email alerts
|

Low Density Lipoprotein Receptor-related Protein 1 (LRP1)-mediated Endocytic Clearance of a Disintegrin and Metalloproteinase with Thrombospondin Motifs-4 (ADAMTS-4)

Abstract: Background: LRP1 is an endocytic receptor of ADAMTS-5 (aggrecanase 2) in cartilage. Results: ADAMTS-4 (aggrecanase 1) is also internalized via LRP1 but at a slower rate than ADAMTS-5. Conclusion: LRP1 differently regulates the extracellular activities of the two key aggrecanases in cartilage. Significance: LRP1 is a major traffic controller of the two aggrecanases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
87
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 66 publications
4
87
0
Order By: Relevance
“…plexes (4), we now know that LRP1 recognizes numerous ligands, including lipoproteins, matrix proteins, growth factors (1,2,5,6), and extracellular proteases (7)(8)(9)(10)(11). Deletion of the Lrp1 gene in mice results in early embryonic lethality at E13.5 (12,13) due to extensive hemorrhaging resulting from a failure to recruit and maintain vascular smooth muscle cells and pericytes in the vessels.…”
mentioning
confidence: 99%
“…plexes (4), we now know that LRP1 recognizes numerous ligands, including lipoproteins, matrix proteins, growth factors (1,2,5,6), and extracellular proteases (7)(8)(9)(10)(11). Deletion of the Lrp1 gene in mice results in early embryonic lethality at E13.5 (12,13) due to extensive hemorrhaging resulting from a failure to recruit and maintain vascular smooth muscle cells and pericytes in the vessels.…”
mentioning
confidence: 99%
“…Previous studies have shown that the C-terminal ancillary domains of TS4 and TS5 govern the specificity of the enzymes by modulating substrate binding (18,19,23) and internalization via lipoprotein receptor-related protein receptors (24,25). The results of studies in HTB-94 chondrosarcoma cells suggest that the CysR domain helps localize TS5 in the extracellular matrix (19), whereas in TS4, the spacer domain is thought to mediate matrix binding (26 -29).…”
mentioning
confidence: 81%
“…Previous studies have shown that the C-terminal ancillary domains of TS4 and TS5 govern the specificity of the enzymes by modulating substrate binding (18,19,23) and internalization via lipoprotein receptor-related protein receptors (24,25). The results of studies in HTB-94 chondrosarcoma cells suggest that the CysR domain helps localize TS5 in the extracellular matrix (19), whereas in TS4, the spacer domain is thought to mediate matrix binding (26 -29 with thrombospondin motifs; Cat, catalytic; CysR, cysteine-rich; Dis, disintegrin; het, heterozygous; mBSA, methylated BSA; MMP, matrix metalloproteinase; MS, mass spectrometry; Pro, N-terminal prodomain; Sp, spacer domain; TS; thrombospondin-type 1 domains; TS5⌬cat, catalytically inactive Adamts5 with an in-frame deletion of exon 3; TS5 null, Adamts5 deficiency created by substitution of exon 2 for an IRES-lacZ-pgk neomycin (Neo) resistance cassette; TS5-FLAG, ADAMTS5 with a C-terminal FLAG tag; TS5-Myc, ADAMTS5 with a C-terminal Myc tag.…”
mentioning
confidence: 99%
“…Subsequently, the disappearance was shown to be due to endocytosis of MMP-13 by LRP1 with the assistance of a 170 kDa MMP-13-specific receptor [59]. Other metalloproteinases currently known to be endocytosed by LRP1 are MMP-9 [60], MMP-9-TIMP-1 complexes [61], MMP-2-thrombospondin 2 complexes [62], proMMP-2-TIMP-2 complexes [63], ADAMTS-4 [64] and ADAMTS-5 [65]. In addition, TIMP-1 [66], TIMP-2 [67] and TIMP-3 [68] can be endocytosed by LRP1.…”
Section: Regulation Of Metalloproteinases and Timps By Lrp1mentioning
confidence: 96%